Effects of inspiratory muscle strength on physiological response to exercise in elite rowers and healthy men - Klusiewicz, A. (Theory and Practice of Physical Culture, 2021)
Objective of the study was to determine the degree of respiratory muscle fatigue in relation to fitness level, and to determine the relationship between inspiratory muscle strength and exercise respiratory indices.